2019
DOI: 10.2131/jts.44.245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the developmental/reproductive toxicity and hepatotoxicity of phthalate esters in rats using an open toxicity data source

Abstract: Phthalate esters (PEs) are widely used as plasticizers in various kinds of plastic products. Some PEs have been known to induce developmental and reproductive toxicity (DART) as well as hepatotoxicity in laboratory animals. In some cases of DART, the strength of toxicity of PEs depends on the side chain lengths, while the relationship between hepatotoxicity and side chain length is unknown. Therefore, in this study, we compared DART and hepatotoxicity in rats, focusing on 6 PEs with different side chains. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Even though phthalates are nowadays regulated in some countries, hundreds of tons are still produced all around the world, and products containing phthalates are still broadly used, leading to ongoing everyday life human exposures. Animal studies suggested that some phthalates cause hepatotoxicity, developmental, and reproductive toxicity [ 52 ] ( Table S2 ). Human phthalate exposures were associated with the increased risks of metabolic disorders, including obesity, diabetes, insulin resistance, and deteriorated liver function [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though phthalates are nowadays regulated in some countries, hundreds of tons are still produced all around the world, and products containing phthalates are still broadly used, leading to ongoing everyday life human exposures. Animal studies suggested that some phthalates cause hepatotoxicity, developmental, and reproductive toxicity [ 52 ] ( Table S2 ). Human phthalate exposures were associated with the increased risks of metabolic disorders, including obesity, diabetes, insulin resistance, and deteriorated liver function [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, similar structure-dependent activity has been observed in the studies reporting adverse developmental effects after treatment with phthalates. Short phthalates (methyl and ethyl) exhibit low or no rodent developmental toxicity, while medium-size phthalates (butyl) increased developmental malformations [ 51 , 52 ]. In agreement with this structure-dependent activity, the phthalates with medium carbon side chains were also found to be the most active in ToxCast assays with the percentage of “active” assays ranging from 7.33% to 26.97% ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, reproductive toxicity is related to the side chain length of phthalates. Phthalate diesters with a side chain length of C4-6, such as DEHP, DBP or BBzP, are able to interfere with reproductive health [ 187 ]. The dose of phthalates can also be the source of conflict in results.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
“…For example, Ha et al [ 181 ] observed that with the increasing dose of DEHP in Sprague-Dawley rats, levels of testosterone, FSH and LH decreased. Some animal species and strains, seem to be less sensitive to phthalate-induced toxicity, and part of this variability may be attributed to differences in phthalate biotransformation [ 187 , 188 ]. For instance, Martinez-Arguelles et al [ 173 ] and Meltzer et al [ 138 ] observed that in female Sprague-Dawley rats, prenatal DEHP exposure at 300 mg/kg/day induced a decrease in estradiol levels.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
“…Due to up-growing demands for lipolytic enzymes in industry, researchers are keen to screen novel lipolytic enzymes from terrestrial and marine environmental samples by metagenomic approaches [20][21][22][23]. Apart from industrial application, esterases are the key enzymes in the degradation of estrogenic phthalate esters, one of the most abundant groups of man-made environmental pollutants, accounting for a number of potential causes of human health problems including developmental and testicular toxicity as well as exhibiting antiandrogenic, teratogenic, and carcinogenic effects [24,25]. Although there are numerous reports on the metabolism of phthalate mono-and diesters in bacteria [26][27][28][29][30], genetic information on phthalate esterases/ hydrolases that catalyzes the first step in the degradation of phthalate ester is quite limited.…”
Section: Introductionmentioning
confidence: 99%